2021
DOI: 10.1021/jacs.0c12731
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Amphiphilic Balance: Changing Subunit Stereochemistry Alters the Pore-Forming Activity of Nylon-3 Polymers

Abstract: Amphiphilic nylon-3 polymers have been reported to mimic the biological activities of natural antimicrobial peptides, with high potency against bacteria and minimal toxicity toward eukaryotic cells. Amphiphilic balance, determined by the proportions of hydrophilic and lipophilic subunits, is considered one of the most important features for achieving this activity profile for nylon-3 polymers and many other antimicrobial polymers. Insufficient hydrophobicity often correlates with weak activities against bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 91 publications
0
31
0
Order By: Relevance
“…59 Their results showed that replacing a small portion of cationic or hydrophobic residues with neutral-polar residues had a minor inuence on antimicrobial potency, but decreased toxicity signicantly. Beyond amphiphilicity, the stereochemistry of the monomers signicantly inuenced toxicity towards eukaryotic cells, 60 which may be related to the different conformational propensities of different enantiomeric monomers: ME-cis: TM (Fig. 2b(6)) with extended conformations showed less toxicity to erythrocytes than the corresponding b-peptides with transconformation.…”
Section: Cationic B-peptidesmentioning
confidence: 99%
“…59 Their results showed that replacing a small portion of cationic or hydrophobic residues with neutral-polar residues had a minor inuence on antimicrobial potency, but decreased toxicity signicantly. Beyond amphiphilicity, the stereochemistry of the monomers signicantly inuenced toxicity towards eukaryotic cells, 60 which may be related to the different conformational propensities of different enantiomeric monomers: ME-cis: TM (Fig. 2b(6)) with extended conformations showed less toxicity to erythrocytes than the corresponding b-peptides with transconformation.…”
Section: Cationic B-peptidesmentioning
confidence: 99%
“…[42][43][44] In analogy, LUVs made of a mixture of 90% of 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) as zwitterionic lipid with 10% of 1,2-dioleoyl-sn-glycero-3phospho-L-serine (DOPS) which is an anionic lipid, were used as a proxy for red blood cell membranes. [44,45] Calcein, here For liposomes mimicking the membrane of E. coli, both S40…”
Section: Dye Leakage Assays Using Liposomesmentioning
confidence: 99%
“…were dissolved in CHCl3 (1 mL). [45] A thin film lipid was leakage activity, Y, using Equation 1: [44] 𝑌 =…”
Section: Fourier-transform Infrared Spectroscopy (Ftir)mentioning
confidence: 99%
“…For example, a study by Gellman et al found that changes in the polymer subunit stereochemistry alter the activity of nylon-3 copolymers [89]; in particular, stereoisomeric monomers bearing either a cis-aminomethyl side chain or a trans-aminomethyl side chain were created and tested for biological activity. The two stereochemical derivatives had an insignificant influence on the antimicrobial activity but demonstrated significant differences in hemolysis (Figure 4a) [89]. McBride et al [90] also described a series of cationic homopolymers comprising only cationic subunits with strong efficacy against vegetative and spore forms of C. difficile.…”
Section: Hydrophobic/hydrophilic Balance and Beyondmentioning
confidence: 99%
“…A study by Boyer C et al [91] concluded that by varying the combinations and order of polymeric blocks, the Beyond amphiphilic balance, several studies have revealed exciting results that could help re-formulate the way antimicrobial polymers are designed to improve activity. For example, a study by Gellman et al found that changes in the polymer subunit stereochemistry alter the activity of nylon-3 copolymers [89]; in particular, stereoisomeric monomers bearing either a cis-aminomethyl side chain or a trans-aminomethyl side chain were created and tested for biological activity. The two stereochemical derivatives had an insignificant influence on the antimicrobial activity but demonstrated significant differences in hemolysis (Figure 4a) [89].…”
Section: Hydrophobic/hydrophilic Balance and Beyondmentioning
confidence: 99%